Epidemiological study of legionellosis in Spain. Year 2023 (Boletín Epidemiológico Semanal, 2024)
Introduction: Legionellosis is a disease of environmental origin transmitted by aerosols of water contaminated with Legionella pneumophila. Legislation for the control of risk facilities and surveillance to early detection of outbreaks are key in their control. We carried out and display the analysis of information from the epidemiological surveillance of legionellosis in 2023.Method: Descriptive epidemiological analysis of legionellosis cases notified in 2023 in Spain. Information from the European network for surveillance of cases associated with travel are also analysed.Results: 2,294 cases were reported, of which 2,265 were autochthonous with a notification rate (RN=4.66). There was a 13.0% increase over the cases in 2022. 1,553 cases were reported in men (RN=6.53, median age 65) and 702 in women (RN=2.83, median age 69) and in ten cases this information was unknown. The highest rates occurred in the age groups 45-64 and 65 and older, both for men and women. The case fatality ratio (CFR) was 8.4% (190/1,553) and increased with age. It was 8.6% (133/1,553) in men and 8.1 in women (57/702).Conclusions: The trend in the number of cases of the disease is increasing. The disease affected more men than women, the elderly and those with risk factors such as smoking or immunosuppression. In addition, for men, the incidence was high in the active stage of life, probably related to some professions or jobs.
Keywords: Legionellosis; Legionella pneumophila; epidemiological surveillance